Fundusze strukturalne a europejska polityka konkurencji - Augustyński, Iwo (Structural Funds from the Perspective of the Competition Policy, 2005)
European Structural Funds play great role for the new members of European Union. Their role in restructurising and developing national economics is hard to overestimate. But actions financed from these Funds are moderated by the Competition Policy especially by regulations concerning state aid and public procurement. The most important regulations are: relating to state aid - de minimis rule, notification procedures, concerning thresholds of supports amount and relating to public procurement clearness rule, concerning object of procurement and publication of calls of proposals. These regulations affect mostly the border between public finances and private companies and assure high effectiveness of public funds.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1071, t. 2, s. 241-251